Acetamide-45 inhibits histamine-and methacholine-induced contraction of isolated guinea pig trachea. - LU Yun-Bin; CHEN Zhong; WU Ming (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effects of the new antiallergic agent N-(pyridin-4-yl)-(indol-3-yl) acetamide-45 (acetamide-45) on histamine- and methacholine-induced contraction of the isolated guinea pig trachea. METHODS: Cumulative histamine or methacholine concentration-contraction studies were carried out in the absence or presence of acetamide-45. Changes in isometric force were measured by force transducers and recorded on a multi-channel polygraph recorder. RESULTS: Acetamide-45 (1 - 30 micromol/L) concentration-dependently inhibited histamine- or methacholine-induced contractile response of isolated guinea pig trachea. At concentrations of 3, 10, 30 mumol/L, acetamide-45 significantly decreased maximum contractile response to histamine by 21 % - 51 %, and EC50 values (95 % confidence limits) were 31.1 (24.4 - 39.8), 34.7(26.8 - 45.0), and 134.4 (82.2 - 220.0) micromol/L, respectively. Similarly, acetamide-45 also inhibited the contraction induced by methacholine in isolated guinea pig trachea. CONCLUSION: Acetamide-45 inhibited histamine- or methacholine-induced contraction of isolated guinea pig trachea, and these effects might be non-specific for either histamine receptor or cholinoceptor.